Implementing safety management systems in aviation - Stolzer, Alan J.; Halford, Carl D.; Goglia, John J. (Ashgate studies in human factors for flight operations, 2011)
In their first book, Safety Management Systems in Aviation, Stolzer, Halford, and Goglia provided a strong theoretical framework for SMS, along with a brief discourse on SMS implementation. This follow-up book provides a very brief overview of SMS and offers significant guidance and best practices on implementing SMS programs. Very specific guidance is provided by industry experts from government, industry, academia, and consulting, who share their invaluable insights from first-hand experience of all aspects of effective SMS programs. The contributing authors come from all facets of aviation, including regulation and oversight, airline, general aviation, military, airport, maintenance, and industrial safety. Chapters address important topics such as how to develop a system description and perform task analyses, perspectives on data sharing, strategies for gaining management support, establishing a safety culture, approaches to auditing, integrating emergency planning and SMS, and more. Also included is a fictional narrative/story that can be used as a case study on SMS implementation. Implementing Safety Management Systems in Aviation is written for safety professionals and students alike.